TEACHING DIVERSE WAYS TO EXPRESS FUTURE IN ENGLISH (Modern education and development, 2025)
Undoubtedly, there many ways to express future tense in English language. However, according to traditional approaches to teaching the English future tense, it is often prioritized the simple structures of "will" and "going to," by ignoring other future tense related verbs. There are  more nuanced expressions of future tense in natural language. This article will explore and provide comprehensive approaches to teaching more interesting ways of expressing future tense in English language.Несомненно, существует множество способов выразить будущее время в английском языке. Однако в традиционных подходах к обучению будущему времени в английском языке часто отдается приоритет простым структурам «will» и «going to», игнорируя другие глаголы, связанные с будущим временем. В естественном языке существуют более нюансированные выражения будущего времени. В этой статье будут исследованы и предложены всесторонние подходы к обучению более интересным способам выражения будущего времени в английском языке.